A workplace exercise intervention in China: an outcome and process evaluation - Lai, Woon Pun Betsy (2018)
The aim of this thesis was to study a worksite exercise intervention for sedentary workers in China. This involved a 10-minute Qigong exercise session twice a day. Four inter-related studies examined the development, implementation, and evaluation of this intervention. First, a feasibility study demonstrated that short exercise breaks could be integrated into the workday routine for employees with sedentary job roles. Second, a pilot study was conducted to test the intervention under research processes. Third, a waitlist controlled trial study showed increases in employees’ physical activity between baseline and post-intervention for intervention (n=193) and waitlist control (n=83) participants, but no changes in work performance or sickness absence. And finally, a process evaluation using RE-AIM framework, i.e. Reach, Effectiveness, Adoption, Implementation, and Maintenance, was conducted using data from focus groups, document analysis, and exercise log reviews. In terms of reach, the exercise intervention was successfully marketed to all employees. In terms of adoption, it was considered that organisational support to implement the intervention was good. The intervention had been implemented broadly as planned. There was high exercise acceptance, but a gradual decrease in exercise adherence through the intervention period. With regard to maintenance, there was no clear management plan to sustain the programme beyond the period of study. To the author’s knowledge, this research is the first to test the effectiveness of worksite exercise in China. It is recommended in future that such interventions focus further on the study of implementation and include outcomes more proximal to the intervention such as job satisfaction and work engagement.